The Possible Incoming Runoff Under Extreme Rainfall Event in the Fenhe River Basin - Jian, Shengqi; Yin, Changyan; Wang, Yafei; Yu, Xin; Li, Yong (Frontiers in Environmental Science, 2022)
Prediction of runoff is of great significance for the sustainable utilization of water resources and flood control and disaster reduction in the basin. In this study, a method for predicting the runoff caused by extreme sub-rainfall events was constructed based on identification of extreme rainfall events, MK Test, R/S analysis, regression analysis. The method was applied to the Jingle sub-basin and the results showed that the extreme precipitation in this basin will keep slight rising trend in future, assuming the climate and underlying conditions remain the same as they were in current. There is a more stable correlational relationship between rainfall characteristic factors and runoff in the extreme rainfall event. The extreme precipitation of 1 to 5 consecutive days under the 100a return period designed by hydrological frequency method is 38.74, 60.01, 66.00, 71.44, 73.69 mm respectively and the possible runoff predicted by the four empirical formulas is 1295-2495, 2108-4935, 2408-5801 and 3051-7062×104 m3 respectively. The rainfall designed by hydrological frequency combination method is 203.64 mm and the possible runoff predicted by the four empirical formulas is 2.8-5.3×108 m3. This study can provide a new reference for predicting the possible incoming runoff under extreme sub-rainfall event.